PTU-004 Hepatocellular carcinoma can be managed safely and effectively in a DGH-setting with superior surveillance-programme survival. (June 2019) - Asad, Muhammad; Bent, Clare; Shawyer, Andrew; Williams, Earl; Stammers, Matthew; Al-shamma, Safa
Abstract : Introduction and aims: HCC is the second commonest cause of cancer-related death worldwide and strongly associated with liver cirrhosis and with a rising incidence. Despite screening most HCC cases present at an intermediate or advanced stage unsuitable for curative surgery. The standard of care for most non-curative cases being actively treated remains transarterial chemo-embolisation TACE and/or ablation (RFA.) Both are specialist procedures normally delivered in tertiary centres. At the Royal Bournemouth Hospital (RBH), a large DGH, specialist HCC treatments are offered to Dorset County following MDT and combined hepatology/IR clinic review. There is an established surveillance programme offered to all suitable at-risk patients. We sought to assess the outcomes of the service with a focus on the benefits of surveillance and the safety of offering tertiary level services in a DGH setting. Methods: We identified all new HCC cases presented in the pan-Dorset Upper GI MDT from Jan 2017 to Dec 2017. We collected demographic data, whether they had been under a surveillance programme and the treatment outcomes including complications and 1- and 12- month mortality. Results: We identified 35 patients (30 M; 5F.) The aetiology was alcohol in 26% (n=9), NASH 43% (n=15), HCV 17% (n=6) and others 9% (n=3.) Cirrhosis was present in 63% (n=22): Child's A 59% (n=13), Child's B 32% (n=7) & Child's C 9% (n=2.) Most cases were referred from RBH 77% (n=27), and 23% from the two other referring hospitals in the County. HCC surveillance detected 43% (n=15) of cases with 57% new presentations. Of the surveillance cases, the majority 87% (n=13) were identified at the centre with the most established surveillance programme but as the largest centre RBH also identified most new presentations 70% (n=14.) More active treatment was offered to the surveillance group at 87% vs 65% of non-surveillance group (p≤0.05.) Curative treatment (transplant, surgery or RFA to small HCC) was suitable in only 14.3% (n=5), all identified by surveillance. TACE was offered to 46% of patients (n=16.) Of the TACE patients, 56% (n= 9) underwent more than 1 procedure. Only 2 patients had decompensation post-TACE, which recovered. Post-TACE survival was 100% at 1 month and 79% at 1 year. These outcomes are comparable to published literature from larger centres. Overall 1-month and 12-month survival for surveillance cases was better than new presentations at 100% and 73% vs 85% and 50% respectively (p≤0.05.) Conclusions: Specialist HCC treatment, following combined hepatology/IR review, can be offered safely and effectively in a large DGH setting with mortality and morbidities outcomes comparable to specialist tertiary centres. Our data confirms HCC surveillance allows for earlier cancer detection with more treatment options and improved survival.